Anterior Abdominal Wall Defects, Diaphragmatic Hernia, and Other Major Congenital Malformations of the Musculoskeletal System in Barbados, 1993–2012 - Singh, Keerti; Kumar, Alok (Journal of Pediatric Genetics, 2017)
This study describes the prevalence and patterns of major congenital malformations of the musculoskeletal system and the resulting morbidity and mortality. It is a retrospective population-based study over the period 1993 to 2012. The overall prevalence of major congenital malformations of the musculoskeletal system was 9.02/10,000 live births. The prevalences of omphalocele, gastroschisis, and diaphragmatic hernia were 2.53, 2.22, and 1.42 per 10,000 live births, respectively. The case fatality ratio for the omphalocele, gastroschisis, and diaphragmatic hernia was 12.5, 28.5, and 67%, respectively. In conclusion, the prevalence rate of the major congenital malformations of the musculoskeletal system was higher than those reported in retrospective studies from other countries and remained static during the study period. These defects were associated with a high mortality rate and contributed significantly to the overall neonatal mortality in this country.
Keywords: Caribbean; congenital malformations; musculoskeletal; prevalence; mortality